THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE EAST JAVA PROVINCE EDUCATION OFFICE - Maqnin, Lailil; Abdul Kodir Djaelani; Supriyanto (Pena Cendekia Insani, 2025)
This study examines the impact of work motivation and work environment on employee performance, with job satisfaction as an intervening variable at the East Java Provincial Education Office. Using a quantitative research method with a survey approach, the study surveyed 62 employees from the office. The findings indicate that both work motivation and work environment significantly and positively influence job satisfaction. Furthermore, work motivation and work environment also have a positive and significant impact on employee performance, both directly and indirectly through job satisfaction. The results underscore the importance of managing work motivation and fostering a supportive work environment to enhance employee performance, which in turn supports the achievement of organizational goals. This research highlights the critical role that motivation and the work environment play in improving employee performance within the public sector, emphasizing the need for organizational strategies that prioritize these factors.